To the question of application of new physical and chemical geotechnologies in the development of uranium ore deposits - Yu. P. Panov; O. S. Bryukhovetsky; A. G. Sekisov (Известия высших учебных заведений: Геология и разведка)
Background. Underground uranium leaching is a promising geotechnological process due to its potential to provide for a radical increase in the technical and economic efficiency, as well as environmental safety, of uranium deposit development. In this article, we discuss the main results in this direction obtained by specialists of the Russian State University for Geological Prospecting.Aim. To study the processes of uranium leaching by activated solutions, which undergo electrophotochemical treatment prior to contacting with the ore.Materials and methods. Activation preparation of leaching solutions enables the synthesis of active hydrated forms of oxygen and hydrogen with collectivized protons and hydroxyl ions clustered by water molecules. Following the stage of pre-oxidation with an active carbonate solution, a model downhole leaching with chloride-hypochlorite, soda, and sulfuric acid solutions was carried out. Testing percolation leaching of uranium from the ores of the Uchkuduk and Sugraly deposits by activated solutions was conducted at laboratory installations designed by the the Russian State University for Geological Prospecting jointly with the Institute of Mining of Far-East Branch of the Russian Academy of Sciences and Zabaikalsky State University. As a result, the potential of a significant increase in uranium extraction was noted.Results. When leaching with sodium carbonate and ammonium carbonate solutions, the uranium extraction from ore samples from the Sugraly deposit comprised 52% and 59%, respectively. At the same time, the use of an activated solution of sodium percarbonate, which combines the functions of an oxidizing agent and a complexing agent, resulted in an 87–88% uranium extraction into productive solutions during 21 days without preliminary pre-oxidation.Conclusion. The results obtained confirm the prospects of using mine (block) and downhole uranium leaching with activated solutions.